2021
DOI: 10.3390/cells10071732
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Induced Dysbiosis Exacerbates IFN-γ Production and Pulmonary Inflammation in the Mycobacterium tuberculosis Infection

Abstract: The microbiota of the gut–lung axis affects local and far-reaching immune responses and might also trigger chronic and inflammatory diseases. We hypothesized that gut dysbiosis induced by obesity, which coexists in countries with a high tuberculosis burden, aggravates the host susceptibility and the pulmonary damage tolerance. To assess our hypothesis, we used a model of high-fat diet (HFD)-induced obesity, followed by infection of C57BL/6 mice with Mycobacterium tuberculosis. We showed that obesity increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Relevant studies have demonstrated a strong link between TB and impaired immune response [53]. One study elucidated another potential regulatory mechanism of the intestine-lung axis [54], suggesting that obesity can lead to dysbiosis of the intestinal flora and dysregulation of the intestinal microenvironment, thereby increasing susceptibility to TB and decreasing tolerance to lung injury. Although some studies have reported that TB is strongly associated with impaired immune response and that the risk for latent TB recurrence is extremely low in immunocompetent patients, the risk for recurrence is, in fact, significantly elevated in this patient population [55].…”
Section: Plos Onementioning
confidence: 99%
“…Relevant studies have demonstrated a strong link between TB and impaired immune response [53]. One study elucidated another potential regulatory mechanism of the intestine-lung axis [54], suggesting that obesity can lead to dysbiosis of the intestinal flora and dysregulation of the intestinal microenvironment, thereby increasing susceptibility to TB and decreasing tolerance to lung injury. Although some studies have reported that TB is strongly associated with impaired immune response and that the risk for latent TB recurrence is extremely low in immunocompetent patients, the risk for recurrence is, in fact, significantly elevated in this patient population [55].…”
Section: Plos Onementioning
confidence: 99%
“…Although complement activation is considered a supportive component of our first line of defense against pathogens, its detrimental (bystander) activation might lead to increased tissue damage and susceptibility to TB. M.tb infected obese mice on a high-fat diet (HFD) demonstrate increased pulmonary inflammation, IFN-γ-mediated immunopathology, and susceptibility to M.tb infection [ 73 ]. Data that link aging, obesity, and TB are so far conflicting.…”
Section: How Comorbidities Of Aging Impact Tb In the Elderlymentioning
confidence: 99%
“…The effect of overnutrition is not as marked as the effect of undernutrition, but while some studies in humans report that, apparently, obesity is related to enhanced resistance to the infection [ 240 , 241 ], studies with mice point to the opposite direction, finding that obesity models obtained by administration of high fat diets deal worse with M. tuberculosis infection and relate this susceptibility difference to the intestinal microbiome change caused by the diet [ 242 , 243 , 244 ]. So, it can be hypothesized that, in the case of overnutrition, as long as the intestinal microbiome, which depends on other factors than the nutritional income of the diet, remains diverse and functional, there might be no additional enhancement of susceptibility, but other parameters must be included to evaluate the status of the host.…”
Section: Tuberculosis: Knowing the Enemymentioning
confidence: 99%